Universalization in the first course of Medicine studies: Experience during the first semester of 2004- 2005. - Margarita Roméu Escobar; Mayra Gil León; Raúl López Fernández (Medisur)
Background: The sliding of the basic cycle of teaching in Medicine speciality to the Health Primary care inserted in the in the university process of the higher medical education es quite brand new , whose development in the practical field was accurately unknown. Objective: to explore the course of the teaching learning process of 1st academic year of the medicine speciality as well as to assess the opinion state of its performers, and to identify achievements and difficultiesduring its development. Methods: a qualitative and transversal section study developed from December 2004 to January 2005 in Cienfuegos province. Its general design is part of a national design and the instruments ans techniques used were previously validated for a previous study developed in Havana city and gathered in a Nationa Workshop. These instruments and techniques are based on surveys to students and professors, direct observation and the achievement of focal groups with the performers of the process. Results: this new model is accepted for students and professors who participate and its advantages and intrinsic values are recognized. Achievements and deficiencies related to didactic, organizative, management of the process and preparation of the institute staff among others are identified. The general development of the process is acceptable and the effort of the professors and the workers is recognized in the implementation of this new model.